2013
DOI: 10.1603/ec13099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <I>Rag1</I> on the Preference and Performance of Soybean Defoliators

Abstract: The Rag1 gene confers antibiotic resistance to soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae), and in 2010, varieties expressing Rag1 were released for commercial use in the United States. We do not know how Rag1 varieties will influence the broader community of defoliating insects that inhabit soybean fields. In 2010 and 2011, the preference and performance of pest insects that defoliate soybeans [Glycines max (L.) Merr] were tested using Rag1 and aphidsusceptible varieties. Three coleopterans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…The amino acid composition of leaf tissue from soybean lines with Rag1 genes is different than that of related plants lacking these genes [53]. Even so, consuming plant tissue from soybean lines with Rag genes did not alter fitness of western corn rootworm larvae ( Diabrotica virgifera virgifera LeConte) [54], and other studies [22,55] concluded that the presence of Rag1 genes had little impact on feeding (preference or defoliation) of several soybean pests within the Coleoptera and Lepidoptera, although in the latter study the authors documented reduced caterpillar growth rates. In contrast, Rich and Koch [23] found that brown marmorated stink bugs [ Halyomorpha halys (Stål)] preferred soybeans with Rag1 , and had lower levels of mortality when reared on pods from Rag1 plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid composition of leaf tissue from soybean lines with Rag1 genes is different than that of related plants lacking these genes [53]. Even so, consuming plant tissue from soybean lines with Rag genes did not alter fitness of western corn rootworm larvae ( Diabrotica virgifera virgifera LeConte) [54], and other studies [22,55] concluded that the presence of Rag1 genes had little impact on feeding (preference or defoliation) of several soybean pests within the Coleoptera and Lepidoptera, although in the latter study the authors documented reduced caterpillar growth rates. In contrast, Rich and Koch [23] found that brown marmorated stink bugs [ Halyomorpha halys (Stål)] preferred soybeans with Rag1 , and had lower levels of mortality when reared on pods from Rag1 plants.…”
Section: Discussionmentioning
confidence: 99%
“…Because soybean aphid biotypes have been found that can successfully colonize and develop on soybeans with Rag genes [17,18], researchers have been investigating pyramided resistance, in which multiple Rag genes are present within the same plant [19,20,21]. There is some information that the presence of Rag genes can impact the behavior and biology of other herbivores associated with soybean [22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Bruner et al. () showed that three species of Lepidoptera – Anticarsia gemmatalis Hübner, Helicoverpa zea (Boddie), and Spodoptera frugiperda (JE Smith) – had decreased weight gain when fed Rag1 aphid‐resistant soybeans, but one other species of Lepidoptera, Chrysodeixis includens (Walker), and three species of Coleoptera – Cerotoma trifurcata Föster, Diabrotica barberi Smith & Lawrence, and Diabrotica undecimpunctata howardi Barber – were unaffected by Rag1 aphid resistance. A separate study found that Rag1 aphid‐resistant soybean had no effect on survival of western corn rootworm, Diabrotica virgifera virgifera Leconte (Dunbar & Gassman, ).…”
Section: Discussionmentioning
confidence: 99%
“…() demonstrated that leaf tissue from Rag1 aphid‐resistant soybean retains resistance to A. glycines after detachment from plants. Furthermore, studies evaluating the effect of aphid‐resistant soybean on other insects have relied on detached plant tissue (Lundgren et al., ; Chandrasena et al., ; Dunbar & Gassman, ; Bruner et al., ). IA3027 and IA3027RA1 soybean were grown in 2014, using standard agronomic practices (Bennett et al., ; Kandel, ) and without insecticide application at the University of Minnesota Experiment Station (Saint Paul, MN, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation